Effect of two-step fermentation by Chrysonilia crassa and Bacillus subtilis on nutritional values and antioxidative properties of agro-industrial by-products as poultry feed ingredients - Sugiharto, Sugiharto; Isroli, Isroli; Yudiarti, Turrini; Widiastuti, Endang; Wahyuni, Hanny Indrat; Sartono, Tri Agus (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This current study was subjected to investigate the influence of two-stage fermentation by Chrysonilia crassa and Bacillus subtilis on nutritional values and antioxidative properties of agro-industrial by-products. Materials and methods: Two-stage fermentation with Ch. crassa (inoculated in advance; single-step fermentation) and B. subtilis (inoculated later; two-step fermentation) was conducted on agro-industrial by-products, i.e., banana peel meals, cassava pulp, and rice bran. The pH measurement, microbial enumeration, proximate, and antioxidant analyses were conducted following 4- and 2-days aerobic incubation with Ch. crassa and B. subtilis, respectively. Results: The pH of banana peels and cassava pulp increased with Ch. crassa-fermentation, but then decreased following B. subtilis-fermentation. Chrysonilia crassa-fermentation did not change, but B. subtilis-fermentation decreased pH of rice bran. The number of lactic acid bacteria was higher in two-stage than in single-stage fermented by-products. Crude protein and fat were higher in fermented than in unfermented banana peels. Crude protein was higher in single- and two-stage fermented, while fat higher in single-stage fermented than in unfermented cassava pulp. Crude fat and ash contents increased with fermentation in rice bran. Single-stage fermentation increased some of amino acids contents in banana peels and cassava pulp. The concentration of polyphenols, tannins, and antioxidant potential of banana peels reduced with fermentation. Total polyphenols and tannins were higher, whereas antioxidant activity was lower in fermented than in unfermented cassava pulp. Total polyphenols, tannins, and antioxidant activity were lower in two-stage than in single-stage fermented and unfermented rice bran. Conclusion: Single-stage fermentation with Ch. crassa improved nutritional characteristics of agro-industrial by-products. http://doi.org/10.5455/javar.2018.e301